A rare manifestation of Fanconi anemia - Pradeep, Pooja; K., Vindhiya; R., Shiji (International Journal of Contemporary Pediatrics, 2018)
Fanconi anemia is an inherited pancytopenia, primarily inherited as autosomal recessive form. It occurs in all racial and ethnic groups. Majority of patients have both physical and haematological abnormalities, about one-third of patients will have normal physical features but abnormal haematological findings and unknown percentage have physical anomalies and normal haematological findings. The diagnosis is based on characteristic physical anomalies and abnormal haematological findings, which is confirmed with a lymphocytic chromosomal breakage study using Diepoxy butane (DEB). The report here is about a two and half years old female child who presented with physical features in the form of short stature, microcephaly, left hypoplastic thumb and congenital heart disease without haematological abnormalities. Chromosomal study was suggestive of Fanconi’s anemia.